Design and Improvement of a Compact Bandpass Filter using DGS Technique for WLAN and WiMAX Applications - Ahmed Boutejdar; Mohamed Amzi; Saad Dosse Bennani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexIn this article, A compact size band pass filter based on octagonal resonators is presented to give sharp response at desired frequency bands along with very low insertion loss. The proposed filter structure is composed of octagonal microstrip resonators, backed by Quasi-Yagi slots ‘Quasi-Yagi Defected Ground Structure’ (Quasi-Yagi-DGS). By controlling the electrical coupling between the octagonal–strip and the Quasi-Yagi-DGS, the bandpass filter’s stopband is optimized for better rejection. The proposed BPF has low insertion loss and compact size because of the slow-wave effect. Meanwhile, sharp rejection bands induced by the presence of two transmission zeros. The simulated center frequency and passband insertion loss are 2.4 GHz and 0.6 dB, respectively.